HDL3 stimulates paraoxonase 1 antiatherogenic catalytic and biological activities in a macrophage model system: In vivo and in vitro studies. (18th September 2014) - Rosenblat, Mira; Volkova, Nina; Aviram, Michael
Abstract We analyzed in‐vivo and in‐vitro high density lipoprotein (HDL) effects on paraoxonase 1 (PON1) antiatherogenic properties in serum and in macrophages. Intraperitoneal injection to C57BL/6 mice of recombinant PON1 (rePON1) + HDL, in comparison to HDL or to rePON1 alone, significantly increased serum PON1 arylesterase activity (by 20%), and serum‐mediated cholesterol efflux from J774A.1 macrophages (by 18%). Similarly, in peritoneal macrophages (MPM) harvested from mice injected with HDL + rePON1 versus rePON1 alone, we observed reduction in oxidative stress (by 11%), increase in cellular PON1 activity (by 14%) and in HDL‐mediated cholesterol efflux (by 38%). Incubation of serum or HDL with rePON1, substantially increased PON1 arylesterase activity, two‐fold more than the expected additive values. HDL2 and HDL3 increased PON1 activity by 199% or 274%, respectively. Macrophage (J774A.1) cholesterol efflux rate significantly increased by HDL3 + rePON1 versus HDL3 alone (by 19%), but not by HDL2 + rePON1 versus HDL2 alone. Oxidation of HDL3 reduced its ability to induce macrophage cholesterol efflux, and abolished HDL3 stimulatory effects on rePON1. Addition of exogenous polyphenol quercetin (60 µM), but not phosphatidylcholine or apolipoprotein A1, to HDL + rePON1 increased PON1 activity (by 404%), increased the ability to reduce oxidative stress in J774A.1 macrophages (by 53%) and to stimulate macrophage cholesterol efflux (by 14%). Upon adding the hypocholesterolemic drug simvastatin (15 µg/mL) to HDL + rePON1, PON1 activity and the ability to induce macrophage cholesterol efflux increased, in comparison to HDL + rePON1. We thus concluded that HDL (mostly HDL3), stimulates PON1 antiatherogenic activities in macrophages, and these PON1 activities were further stimulated by quercetin, or by simvastatin. © 2014 BioFactors, 40(5):536–545, 2014